ANALISIS PENGENDALIAN KUALITAS PRODUK KERTAS DENGAN MENGGUNAKAN METODE SIX SIGMA, FTA DAN FMEA UNTUK USULAN PERBAIKAN KUALITAS PRODUKSI - Winarni -; Joko Susetyo; Sariyono _ (PROSIDING SNAST, 2018)
PT Papertech Indonesia unit II Magelang is a company that produces recycled paper with mixed raw materials (short fiber paper such as magazines, newspapers, books), occ (long fiber paper such as dos, cartons) and other additives such as tapioca starch. Its flagship product is chip board. This paper product is often produced every day and always found defect every month resulting in decreased quality (downgrade).Thereforeit is necessary to control product quality. The Six Sigma method is used to measure Sigma Quality Level (SQL) based on the Disabled per Million Opportunity (DPMO) value of chip board production process. Failed Tree Analysis Method is used for defective product defects, the result is used as a barrier to make improvements. The proposed improvements are prioritized based on the largest Risk Risk Number (RPN) in the Failure and Securities Analysis (FMEA) approach and corrective actions with 5W + 1H tools. Based on the calculation, the average value of Defect per Milion Opportunity (DPMO) is 8,950, so the average Sigma Quality Level (SQL) of PT Papertech Indonesia unit II Magelang is 3.87. Fault Tree Analysis shows 13 failure modes that cause the product defect. There are 9 failure modes that prioritize improvement based on Risk Priority Number (RPN) value: hot room temperature (294 RPN), fatigue (280 RPN), decreased concentration (210 RPN), less accuracy (210 RPN), dirty dryer (210 RPN), trim goes into cutter (210 RPN), noise (180RPN), less inspection (180 RPN), moist paper (168 RPN).